O amador e a fotografia: o papel da produção amadora no desenvolvimento fotográfico - Alarcon, Luciano Denardi (2008)
After the golden age of photography s club, the amateur photographer was demoted to the category of mere user of the photographic cameras. But the history of photography shows that this is a great injustice, because the amateur production always had a fundamental importance in the development of photography. After all, while a professional photographer was produced portraits in studios, the amateurs developed new techniques and languages. This dissertation main goal is to see what extent it is possible to differentiate the professional production of amateur production only comparing the imagetic result obtained by each of them. Through interviews, conducted between 2006 and 2008, and analyzing the production of photographic professionals and amateurs, we noticed that the professional and amateur categories have become inadequate to handle the large imagetic production generated from use with the photographic digital cameras and disseminated on the Internet. Today, with the use of digital equipments, we are active participants and witnesses of the formation of a new photography s club movement in the computer network. This new amateur production deserves a watchful eye, because brought in the light of knowledge photographic, a public that simply recorded moments with the cameras. Under the question of piece of art s unity proposal by Walter Benjamin and the communicology of Vilém Flusser, we come to the conclusion that what makes the difference in the development of thinking and producing photographic is the relationship of the photographer with the equipment. Since, with increasingly intuitive cameras, produce a beautiful photograph is easy. Therefore today, be a photographer is work more with ideas than with techniques